JUBILEE OF FRUITFUL COOPERATION OF THE DEPARTMENT OF PHTHISIOLOGY IFNMU AND REGIONAL PHTHISIOPULMONOLOGY CENTRE - Зозуляк, В. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The article presents the materials of the close cooperation of the department of phthisiology IFNMU with Regional Phthisiopulmonology Centre, which is based 31.12.1991 year on the basis of the Ivano-Frankivsk regional tb dispensary. In the historical aspect highlighted the close cooperation of the staff of the department and employees of the Regional Phthisiopulmonology Centre in medical-diagnostic, scientific, educational and preventive activities. Indicated on the achieved significant progress in the fight against the epidemic of tuberculosis in the Carpathian region.